Renal autotransplantation: a solution for different complex situations - Sousa,Pedro Pinto (2021)
Abstract Introduction: Renal autotransplantation (RA) is a safe and effective procedure to reconstruct the urinary tract which first successful surgery was performed by Hardy in 1963. The main indications reported to perform a RA generally include renovascular disease, ureteral pathologies and neoplastic disease. Furthermore, RA may be useful as an ultimate recourse in preventing kidney loss in highly selected patients, especially when conventional methods have failed. Materials and Methods: The authors describe four total different situations where the RA was the key solution for the pathology initially presented. Clinical case I - A 52 years old male with a previous history of left nephrectomy due to a preceding exacerbation of his basal Crohn's disease and also a right ureter cutaneostomie, presented now with repetitive urinary tract infections that led to renal function impairment; Clinical case II - A 57 years old female with the diagnosis of renal artery aneurysm while being studied as a potential kidney donor; Clinical case III - A 49 years old male admitted in the emergency room after a penetrating trauma which conditioned bowel and ureteral lesions with postoperative consecutive and recurrent peritoneal infections that compounded a necessity for a left ureterostomy, that the patient vehemently refused; Clinical case IV - A 24 years old female with the diagnosis of Nutcracker syndrome identified after being studied regarding repetitive urgency admissions with frank haematuria. Results: Every patient was submitted to laparoscopic nephrectomy, ex-vivo reconstruction, if necessary, and kidney transplantation to the iliac fossa. The interventions were uneventful and only one patient faced a minor post-operative complication (surgical wound dehiscende). We performed an ultrasound and renal scintigraphy evaluation on following days after each procedure to attest normal renal perfusion. Discussion: The RA were conducted in two patients with ureteral cutaneostomie because there was no viable alternative but kidney loss. The other two clinical cases were treated with RA because they concerned a complex renovascular disease (one arterial and the other venous). Despite the existence of an endovascular option for these patients, long term follow-up studies are still lacking. Conclusion: The RA is a viable option in specific situations for kidney salvage. The recent development of laparoscopic nephrectomy significantly decreased the surgical hostility to the patient and promoted the RA as a value option for the treatment of complex vascular pathologies, traumatic disease and specific medical situations. It represents a credible alternative with attested results already described in the literature thus requiring a vast Institutional experience with conventional renal transplantation.